2016
DOI: 10.1074/jbc.m116.731638
|View full text |Cite
|
Sign up to set email alerts
|

AcsF Catalyzes the ATP-dependent Insertion of Nickel into the Ni,Ni-[4Fe4S] Cluster of Acetyl-CoA Synthase

Abstract: Acetyl-CoA synthase (ACS) catalyzes the reversible condensation of CO, CoA, and a methyl-cation to form acetyl-CoA at a unique Ni,Ni-[4Fe4S] cluster (the A-cluster). However, it was unknown which proteins support the assembly of the A-cluster. We analyzed the product of a gene from the cluster containing the ACS gene, cooC2 from Carboxydothermus hydrogenoformans, named AcsF Ch , and showed that it acts as a maturation factor of ACS. AcsF Ch and inactive ACS form a stable 2:1 complex that binds two nickel ions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 59 publications
(83 reference statements)
0
15
0
Order By: Relevance
“…6). Many CODH loci code for a nickel-inserting accessory protein, which is believed to facilitate the insertion of nickel into the CODH active site (40). Here, expression of the nickel-inserting accessory protein CooC from C. carboxidivorans did increase activity, but only in the case of no nickel supplementation.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…6). Many CODH loci code for a nickel-inserting accessory protein, which is believed to facilitate the insertion of nickel into the CODH active site (40). Here, expression of the nickel-inserting accessory protein CooC from C. carboxidivorans did increase activity, but only in the case of no nickel supplementation.…”
Section: Discussionmentioning
confidence: 74%
“…Recently, Gregg et al showed the necessity of a nickel accessory protein, AcsF, to facilitate the insertion of nickel into the active site in Carboxydothermus hydrogenoformans (40). Even though we tested our system with additional expression of the AcsF accessory protein, the in vivo carbon exchange reaction could not be detected.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…CO+normalH2OCO2+2normale+2normalH+ΔG0=20kJ·mol1the aerobic and anaerobic CODH enzymes have different subunit structures, different cofactors and are not related at the amino acid sequence or structural level []. Prokaryotes that use aerobic CODH use CO as a source of electrons in energy metabolism, are typically aerobes or facultative aerobes and tend to transfer the electrons from CO to high potential acceptors such as O 2 or acceptors derived from it such as nitrate (NO 3 − ) .…”
Section: Resultsmentioning
confidence: 99%